BNT162b2 COVID-19 vaccination elicited protective robust immune responses in pediatric patients with inborn errors of metabolism - Zubarioglu, Tanyel; Dinc, Harika Oyku; Hopurcuoglu, Duhan; Gulmez, Ruveyda; Uygur, Esma; Yilmaz, Gizem; Ahmadzada, Saffa; Uzunyayla-Inci, Gozde; Oge-Enver, Ece; Kiykim, Ertugrul; Kocazeybek, Bekir; Aktuglu-Zeybek, Cigdem (Frontiers in Immunology, 2023)
SARS-CoV-2 infection can lead to an even life-threatening acute metabolic decompensation in children with inborn errors of metabolism (IEM), so vaccination is mandatory. However, IEM can affect innate or adaptive immunity and the impact of immune system alterations on immunogenicity and vaccine efficacy is not known. Here, we investigated humoral immune responses to the BNT162b2 mRNA COVID-19 vaccine and clinical outcomes in pediatric IEM patients. Participants who were 12-18 years of age, had a confirmed diagnosis of IEM, received BNT162b2 were enrolled. Anti-SARS-CoV-2 Immunoglobulin G (IgG) and SARS-CoV-2 neutralizing antibody (nAb) titers were measured to assess humoral immune response. Six months after the second dose of BNT162b2, patients were surveyed about whether they had a post-vaccine COVID-19 infection. Fifteen patients were included. A complete Anti-SARS-CoV-2 IgG seropositivity and nAb IH% positivity was observed in all patients after second dose. Anti-SARS-CoV-2 IgG titers response to vaccination were significantly increased in IEM patients. Anti-SARS-CoV-2 IgG titers and nAb IH% increased significantly after the first dose. The increase in antibody titers after first and second vaccination remained significant in COVID-19 naïve patients but did not differ in recovered patients. Vaccination appears to be clinically effective in IEM patients, as none of the patients had COVID-19 infection within six months of the last vaccination. Humoral immune response after two doses of BNT162b2 in pediatric IEM patients was adequate and the immune response was not different from that of healthy individuals.